MATHEMATICAL INDUCTION

Asked by sukhmaneet | 12th Aug, 2009, 11:27: PM

Expert Answer:

let the given statement be p(n)

it's clear that p(1) is true.

 assume that p(k0 is true

 we will prove p(k+1) is true

 since p(k0 is true , we have

kth term is a+(k-1)d

now k+1) th term = kth term+the common diff d

=a+(k-1)d+d

=a+kd

=a+[(k+1)-1]d

so we have proved that k+1 the term is a+[(k+1)-1]d

so p(k+1) is true.

Answered by  | 12th Aug, 2009, 11:44: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.